Effect of remote live broadcast of Traditional Chinese Medicine health preservation techniques on relieving anxiety of the quarantined people entering China (远程直播中医养生功法缓解入境集中隔离人群焦虑的效果观察) - CHEN Ruyan (陈如燕); WU Yujing (吴玉静); YAN Haijun (严海君) (Association of Integrative Nursing, 2022)
Objective To explore the alleviating effect of remote live broadcast of Traditional Chinese Medicine (TCM) health preservation techniques on anxiety of the quarantined people entering China. Methods From September to October 2021, 320 inbound quarantined people in a centralized quarantine site in Hongkou District, Shanghai were selected as the research subjects, and they were divided into observation group (n=160) and control group (n=160) according to random number table method. The control group received routine entry management, and on this basis, the observation group was implemented remote live broadcast of TCM health preservation techniques, and the psychological anxiety levels and nursing service satisfaction of the two groups were compared. Results Two weeks after intervention, the self-rating anxiety scale (SAS) score of the observation group was (38. 64±6. 15) points, lower than that of the control group (46. 18±5. 48) points, the difference was statistically significant (P<0. 01). The nursing service satisfaction of the observation group was higher than that of the control group, and the difference was statistically significant (P<0. 01). Conclusion During the centralized isolation, the quarantined personnel were guided to exercise health preservation techniques of TCM by way of remote live broadcasting. As a TCM-characterized management mode for concentrated quarantine, the remote live broadcast of TCM health preservation techniques is potentially effective to promote the physical and mental health of isolated personnel, relieve psychological pressure, and improve the satisfaction of nursing services. (目的 探讨远程直播中医养生功法对入境集中隔离人群焦虑的缓解作用。方法 将2021年9月入境隔离人员160名设为对照组, 实施常规入境隔离管理; 将2021年10月入境隔离人员160名设为观察组, 在对照组基础上开展远程直播中医养生功法。观察两组干预前后的焦虑情绪, 比较两组对隔离点护理服务的满意程度。结果 干预后, 两组焦虑自评量表(SAS)评分均降低, 且观察组SAS评分(38. 64±6. 15)分, 低于对照组的(46. 18±5. 48)分, 差异有统计学意义(P＜0. 05)。观察组对护理工作的满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 集中隔离期间以远程直播形式引导隔离人员进行中医养生功法的锻炼, 形成具有中医特色的隔离点管理模式, 能有效促进隔离人员身心健康, 缓解心理压力, 提高护理服务的满意度。)